KNOWLEDGE ATTITUDE AND PRACTICES OF HEALTH WORKERS TOWARDS HAND WASHING AT LACOR HEALTH CENTER III OPIT. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Wamala, Adam Johnson (Student's Journal of Health Research Africa, 2023)
Background. Purpose: The purpose was to assess the knowledge, attitude, and practices of health workers toward hand washing at Lacor Health Center III Opit. Objectives: To evaluate the level of knowledge of health workers about hand washing at Lacor Health Center III Opit. To establish the attitude of health workers towards hand washing at Lacor Health Center III Opit. To assess the practices of health workers towards hand washing at Lacor Health Center III Opit Methodology: A descriptive cross-sectional study design was used in the collection of data because the design allowed data to be collected at one point in time Results: On average 81.2% of the respondents had good knowledge of hand washing and 18.2 of the health workers had little knowledge of hand washing. The majority of the health workers on average 78.4% had a positive attitude towards hand washing and 21.6% of the respondents had a negative attitude towards hand washing. The majority of the health workers on average 72.75% contrarily had poor practices towards hand washing while only 27.25% of the respondents had good practices towards hand washing Conclusion: In conclusion, many of the health workers had good knowledge and positive attitude toward hand washing respectively. However, given the vast knowledge and positive attitude, the majority did not apply the knowledge in practicing hand washing. This meant that HAI was still high since few HWs practiced hand washing. Recommendations: Hand washing at Lacor Health Center III Opit should be put as a goal in the year planner so that the rate of HAIS goes down. Still, several hand washing facilities like soap, water tanks, water sources, detergents, and others have to be put in place at the facility to enable the process of hand washing.